Radiation-induced effects on bone marrow of bank voles inhabiting the Chornobyl exclusion zone. (3rd August 2022) - Lypska, Alla; Riabchenko, Natalia; Rodionova, Natalia; Burdo, Olena
Abstract: Purpose: To investigate the effects of chronic exposure to low-dose radiation on bone marrow (BM) hematopoiesis of bank voles inhabiting the radioactively contaminated territory of the Chornobyl exclusion zone. Materials and methods: Animals were collected within the highly radioactive area of the so-called Red Forest located close to the destroyed 4th reactor of the Chornobyl Nuclear Power Plant. Radioecological investigations included evaluation of radiocontamination of soil samples by 90 Sr and 137 Cs, levels of incorporated radionuclides in animals' bodies and organs, as well as the absorbed dose rates. The study of peripheral blood and BM parameters combined with cytogenetic analysis of BM micronucleated polychromatic erythrocytes (MNPCEs) and standard metaphase test was carried out. Results: The blood system of the exposed animals manifested significant changes in peripheral blood parameters (anemia and leucocyte formula left shift), ineffective differentiation, and maturation of BM cells, particularly relevant to the erythroid and granulocyte pools. Increased yields of BM MNPCEs and chromosomal aberrations, including dicentrics (dics) and Robertsonian fusion-like configurations (Rbts), were revealed. Conclusions: Observed disturbances in the BM and peripheral blood suggest functional instability and inefficient compensatory and recovery reactions of the blood system of the bank voles from the contaminated areas of the Chornobyl exclusion zone. We assume that they are the consequences both of direct radiation exposure and hereditary pathological changes that have formed in a number of generations inhabiting radioactively contaminated areas.